Furosemide ethanol-free oral solutions for paediatric use: formulation, HPLC method and stability study. Issue 3 (2nd August 2017) - Zahálka, Lukáš; Klovrzová, Sylva; Matysová, Ludmila; Šklubalová, Zdenka; Solich, Petr
Abstract : Background: Oral liquid solutions of the diuretic active ingredient furosemide (FUR) marketed across Europe do not comply with recent requirements for paediatric preparation owing to their ethanol content and, moreover, in some countries only tablet or injection dosage forms of furosemide are available. Objectives: To formulate extemporaneous paediatric ethanol-free solutions of FUR (2 mg/mL) with suitable solubility in the aqueous vehicle and an acceptable taste and to evaluate their stability under two different storage conditions during a 9-month study period. Methods: Our work presents two developed formulations of FUR ethanol-free paediatric oral solutions 2 mg/mL for easy extemporaneous compounding in a pharmacy. FUR solubility avoiding the use of ethanol was achieved using sodium hydroxide (formulation F1) or disodium hydrogen phosphate dodecahydrate (formulation F2). The preparations were stored at 25°C±3°C or at 40°C±0.5°C and protected from light. For FUR and preservative, methylparaben (MP), a stability assay was conducted by a high-performance liquid chromatography validated method and determination of pH stability. Results: The remaining FUR concentration was >90% of the initial concentration after 270 days in both formulations at both storage conditions, 25°C and 40°C. The concentration of MP decreased significantly in the formulation F2 stored at 40°C. Conclusions: Both formulations were stable when stored at room temperature for up to 9 months; formulation F1 was stable even at 40°C. MP used as an antimicrobial agent fully satisfied the recommended criteria for preservative efficacy in oral preparations according to the European Pharmacopoeia 9.0 (5.1.3).